If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3w-39=9(w+5)
We move all terms to the left:
-3w-39-(9(w+5))=0
We calculate terms in parentheses: -(9(w+5)), so:We get rid of parentheses
9(w+5)
We multiply parentheses
9w+45
Back to the equation:
-(9w+45)
-3w-9w-45-39=0
We add all the numbers together, and all the variables
-12w-84=0
We move all terms containing w to the left, all other terms to the right
-12w=84
w=84/-12
w=-7
| 2/5x-10=-20 | | 3(2d+2)-11=34 | | (11x-2)(3x-4)=0 | | C=8/7(k-35) | | -34=-y/5 | | -50=m+-3 | | 12g=1×(2/3g-1)+11 | | -4-9x=-4+6 | | -8x=0.11 | | w/4=-38 | | -3(5-3x)-7x=-43 | | -5(g+10)-1=24 | | -34=t-9 | | 7-18x=17-17x | | 4-x/2=1 | | 2x+7=−5+x | | −99=−9(9+x) | | 3t+2+6=36 | | 7+-12V=6+v | | 5a+2a=84 | | 6x-1=5+ | | 4-1/2m=10 | | 5x+15=8x-8 | | 5+2+3=-(x-4) | | -6w-8=-4(w+6) | | 2+12x=170 | | d/2+14=17 | | 41+k=-2k+2 | | 70-2y=-9y | | 5x-7=-2(5x-4) | | -26=m-3 | | 3(x+10)=2x+3x-8 |